Calculation of the cross section for the reaction γ³He → pd at intermediate photon energies - Kotlyar, V.V.; Belyaev, A.A. (Вопросы атомной науки и техники, 2001)
The differential cross section and the asymmetry coefficient for the two-body photodisinteration of ³He by linearly polarized photons are calculated with wave functions for Bonn potential. Dependences of the observables on the components of the ³He wave function with the orbital angular momenta L, l ³ 1 are studied at photon energies Eg up to 300 MeV.